FEMALE CHARACTER’S STRUGGLE TO GET SYMBOLIC CAPITAL IN DAISY GOODWIN’S THE AMERICAN HEIRESS - Widyaiswara, Tiara (Universitas Islam Lamongan, 2020)
The female characters struggle in The American Heiress is very interesting to be analyzed because the story tells about the sacrifice love which containing of contestation desired multicultural identities. This study is aimed to analyze the struggles of female characters to get symbolic capital which focus on Cora Cash and Charlotte symbolic struggle to be the new Duchess. To support this study, the practice of theory by Pierre Bourdieu is used as a concept of the symbolic struggle which involved to the contestation each character. This study applies qualitative research study. The result of this study is Cora Cash and Charlotte are done the struggle, they have different amount of the capital which Cora is more accomplish all of the capitals than Charlotte. It can be seen by the movement of Cora’s position is different before and after she goes to England. Her first coming to England she is the new comer, she tries to show her strategy until she gets the symbolic capital as the wife of the Duke.